Effects of synthesis conditions on photocatalytic activity of g-C3N4 - An Tran Doan; Phuc Nguyen Van; Tri Ngoc Nguyen; Hung Nguyen Phi; Vien Vo (My University, 2017)
Effects of synthesis conditions on photocatalytic activity of g-C3N4
Keywords: g-C3N4; Photocatalytic activity; Synthesis conditions